Kompetensi Manajerial Kepala Sekolah, Motivasi Kerja, dan Lingkungan Kerja: Pengaruhnya terhadap Kinerja Guru - Wiwit Fatkurinah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
Performance is the quantity or quality of something produced or services provided by someone doing the job. Performance is the result or level of success of a person as a whole during a certain period in carrying out a task compared to various possibilities, such as standard work results, targets or targets or criteria that have been agreed upon in advance. The purpose of this study was to determine and analyze the effect of principal managerial competence, work motivation and work environment on teacher performance at SMKN Sub Rayon 2, Pasuruan Regency. The population in this study were 165 people from SMKN Sub Rayon 2 Kab. Pasuruan. The sampling method using probability sampling technique used in this study is the cluster sampling method because this study has a large population area. The results showed that the Principal Managerial Competence (X1), Work Motivation (X2), and Work Environment (X3) had a significant effect both partially and simultaneously on the teacher performance variable (Y). The principal managerial competence variables, work motivation, and work environment were able to explain the teacher performance variables by 57.3%.